Ecuadorian public high school teachers146 perceptions on technological resources used by teachers in their EFL classrooms during the COVID19 pandemic - Chimarro Guacán, Elizabeth Liliana (2021)
Resumen:The Ecuadorian public high school teachers’ perceptions on technological resources used by teachers in their EFL classrooms during the COVID-19 pandemic has the objective to analyze the technological resources used by teachers in their EFL classrooms during the COVID-19 pandemic. The participants were ten in-service English teachers of the Senior high-school section of different public high schools from Quito and Machachi, Pichincha, Ecuador. Both quantitative and qualitative approaches were carried out to develop this research study. The data was obtained through an online resource called “Microsoft Forms” that contained two surveys and a structured interview. The gathered results from the research instruments were presented in three statistical tables; besides, they were examined and described. Based on the results, it was possible to conclude that teachers use diverse technological resources to teach English and have positive perceptions towards them because they facilitate the teaching process and help to develop students’ language skills. Nevertheless, external barriers like lack of Internet connection and lack of technological devices were found that might affect the teaching process, as well as, the teachers’ attitudes towards technologies.